2016
DOI: 10.1039/c5sc04906g
|View full text |Cite
|
Sign up to set email alerts
|

Catenation and encapsulation induce distinct reconstitutions within a dynamic library of mixed-ligand Zn4L6 cages

Abstract: Subcomponent self-assembly generates dynamic combinatorial libraries of Zn4L6 cages whose composition is strongly affected by catenation and encapsulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 61 publications
(32 reference statements)
0
23
0
1
Order By: Relevance
“… 18 Modulating the binding strength of the templating guest can reorganise product mixtures to express specific products. 19 A template can also generate a set of well-defined structures, instead of a single product. 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 Modulating the binding strength of the templating guest can reorganise product mixtures to express specific products. 19 A template can also generate a set of well-defined structures, instead of a single product. 20 …”
Section: Resultsmentioning
confidence: 99%
“…We envisage applicability in the areas of asymmetric catalysis 6h , 25 and guest-specific receptor design. 19 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…Nitschke and co-workers reported the synthesis and self-sorting of two related tetrahedral cages, [Zn 4 1 6 ] 8+ and [Zn 4 17 6 ] 8+ , prepared by sub-component self-assembly of Zn II and NDI ( S1 ) or porphyrin-derived ( S17 ) subunits. 65 A study of the host–guest properties revealed that each cage can respond to a different stimulus; the electron-poor NDI units of [Zn 4 1 6 ] 8+ were found to thread up to two electron-rich crown-ether macrocycles, while [Zn 4 17 6 ] 8+ was found to accommodate a C 70 guest in its cavity ( Fig. 12a and b ).…”
Section: Assembly-dependent Integrative Self-sortingmentioning
confidence: 99%
“…[10,11] These analytical limitations become even more severe when the knotted or catenated structures are formed in complex mixtures of (quickly) interconverting dynamic combinatorial libraries, [12] in which multiple species coexist. [13] Ac hange of conditions,f or example,t emperature, pH, concentration, or solvent, may then lead to shifts of the equilibrium to other topologies. [2] Fore xample,P rakasam et al [14] observed at ransformation of at refoil knot into aH opf link, when the temperature was raised.…”
mentioning
confidence: 99%